The Effectiveness of Google Classroom on Hybrid Learning in Junior High School - Robbi Rahim; Adri Lundeto; Elihami Elihami; Agus Riyanto (AL-ISHLAH: Jurnal Pendidikan, 2022)
Teachers use Google Classroom for online learning so that learning continues despite the policy of learning from home and the existence of distance restrictions. This study aims to analyze the use of Google Classroom in online learning. This study uses a quantitative survey method involving 84 students and 5 teachers. Research data collection through surveys containing several questions assisted through Google Forms. Likert scale questionnaire (1-5) was used to collect data on student perceptions of teacher teaching skills, implementation, barriers to learning, and student satisfaction. Qualitative data were analyzed by descriptive technique. The results of this study indicate that Hybrid Learning by utilizing Google Classroom, especially online learning is able to effectively support the learning process based on teacher teaching skills data by 85%, learning implementation by 85%, and student satisfaction by 97.6%. Thus, Google Classroom is the right application for teachers to use in online learning and distance learning. The obstacles in online learning can be optimized through classroom learning. Suggestions for further research is to develop teaching materials both printed and electronic using Google Classroom.